Perlindungan Hukum Konsumen Pengguna Obat Tradisional Tanpa Izin Badan Pengawas Obat dan Makanan (BPOM) yang Diedarkan Secara Daring Pasca Pandemi Covid-19 - Devia Oktaviandra; Yeti Sumiyati (Jurnal Hukum Lex Generalis, 2025)
Law Number 8 of 1999 concerns Consumer Protection in protecting and guaranteeing legal certainty for a business to carry out production with security, comfort, safety, good quality, and health. Maintaining health is essential for humans, especially during the COVID-19 pandemic and after the pandemic ends. The public consumes traditional medicine because of its effect, which can increase the body's immunity during the pandemic. Getting traditional medicine during the COVID-19 pandemic is very easy from online shops. This is what we used to do until the pandemic ended. The government the existence of Consumer Protection Law No. 8 of 1999 as a basis for protecting consumer safety rights and supervision of BPOM No. 8 of 2020, which monitors medicine and food distributed online. The discovery of traditional medicine preparations by BPOM Public Relations and BPOM's annual case report without a distribution permit online will violate consumer rights. The research method used is a normative juridical legal approach by examining statutory regulations, library materials, or secondary data as a basis for research accompanied by interviews related to the problems studied. The results of the research found that the provisions for the use of traditional medicines according to Law No. 8 of 1999 concerning consumer protection are linked to BPOM Regulation No. 8 of 2020 concerning the supervision of medicines and food distributed online in the current situation the COVID-19 pandemic is very necessary because in general it has been regulated in the UUPK by ensuring that the actions taken by BPOM in implementing the Law's policies are repressive and preventive. That is why the government issued a consumer protection law that benefits the population so that they have legal force against consumer losses committed by business actors. The responsibilities that consumers expect from business actors regarding UUPK No. 8 of 1999, namely being obliged to provide compensation to customers for damage, contamination, and use of products that consumers use.